(untitled) (Journal of Hama University, 2020)
This research was carried out in Ain Aljrn, Al-ghab, Hama, and Province during the two agricultural seasons 2016 and 2017. The experiment was conducted in an open field. This research included variety of hybrid muskmelon (Cucumis melo L.) Natasha F1, were grafted on many hybrids rootstocks pumpkins, (Forza F1, Jwad F1 and one locally rootstock pumpkin Lagenaria siceraria). The results showed the superiority of the muskmelon hybrids Natasha F1, which is grafted on the hybrid rootstock Forza F1 in the main stem length (228.20)/cm, and the largest number of leaves (231.10)/leaves /plant, the area leafy (17807)/cm²/plant, the number of branches (6.25)branch/Plant. And the largest number of feminine blossoms, 22.36 on the plant, and number of fruit, (4.05) fruit/plant, and gave high productivity (8.69) TN/Dunm. The results indicate a strong positive correlation between vegetative and characteristics of fruit growth, and the correlation between leaf surface area and productivity is strongly positive (r = 0.92).